A Combined Interleaving Technique for Trellis Coded MPSK Systems in Rayleigh Fading Channels - Öztürk, Ersin; Aygölü, Ümit (Springer Science and Business Media LLC, 2001)
Freedom of mobility is the latest trend in the evolution of digital communication systems. In these systems bandwidth and power constraints limit the mobility of the users. TCM (trellis coded modulation) is a combined coding and modulation scheme which increases the productivity of a digital communication system without increasing the transmitted power or the required bandwidth. A mobile communication channel is affected from noise and fading because of the multipath propagation. On a Rayleigh fading channel, coding should be used with techniques which uncorrelate the received energy of each consecutive coded symbol. Interleaving is one of these techniques and used to make burst errors into random errors which can be corrected by error correcting codes. In this paper, the trellis coding system which combines a regular convolutional encoder, bit interleaver, coordinate interleaver, and an appropriate decoder is considered. The analytical bit error probability upper bounds are derived for the 8-PSK TCM system whose diversity is increased by using a regular 2/3 rate convolutional code followed by three bit interleavers and a 8-PSK signal mapper followed by two coordinate interleavers. The analytical and simulation results show that to increase the diversity of the trellis coded M-PSK systems in Rayleigh fading channels is the primary key for reliable transmission of high quality voice and digital data.